A Study on the Rational Positioning of O-cell Boxes in Three Test Piles considering the Geology of Ho Chi Minh City, Vietnam - Bach, Lan Vu Hoang (Engineering, Technology & Applied Science Research, 2025)
The O-cell pile test has more advantages than the traditional loading test because it does not require a cumbersome reaction frame, counterweight, or anchor piling. Therefore, the cost of pile testing is dramatically reduced compared to top-down tests. The most essential aspect of the single-level bidirectional cell test is precisely determining the location of an O-cell box. This paper addresses inaccuracies in placing O-cells in bidirectional loading test results on full-scale, large-dimension, high-capacity barrettes test piles from three different projects in Ho Chi Minh City, Vietnam. Detailed analysis shows that the pile toe response is very small, the movement of the upper piles is relatively minor, and the skin friction along the pile segments is not fully mobilized. Research results indicate that the O-cells must be moved up to better predict the ultimate soil pile resistance. Therefore, the condition for placing the O-cell box at the load-balance plane is only a necessary condition. For better placement of the O-cell, the settlement-balance plane may be additionally considered as a sufficient condition and will be researched in future work.